A PROSPECTIVE NON-RANDOMIZED STUDY OBSTRUCTION OF GASTRIC OUTLET: OUTCOMES OF ANTRODUODENAL STENTING. - Keshari, Ravi (Student's Journal of Health Research Africa, 2023)
Background: The advanced stage of gastric cancer is commonly characterized by gastric outlet obstruction (GOO), extrinsic lymph node compression, and pancreaticobiliary malignancy. The patient presents with symptoms of gastric discomfort, postprandial epigastric fullness, and recurrent abdominal pain. The act of emesis can lead to significant consequences such as severe dehydration, malnutrition, and a diminished quality of life (QoL). Endoscopic enteral stent implantation has gained recognition as a viable alternative treatment modality for malignant gastric outlet obstruction (GOO) due to its favorable safety profile, minimal invasiveness, and cost-effectiveness. Method: For five years, a prospective, non-randomized study was conducted on Patients who had a gastric outlet obstruction (GOO) and weren’t candidates for surgery because of the procedure’s high morbidity, refusal, or low nutritional status were suitable if they were over 18. The stent that was utilized was a Wallflex by Boston Scientific Corporation, MA, United States, exposed SEMS with a diameter of 27 mm (22 mm at the mid-body) and lengths of 60, 90, or 120 mm preloaded in a 10 Fr delivery system Result: The presence of Gastric Outlet Obstruction Score (GOOS) 1 was observed in three instances 8 instances (53.33%) of those with laboratory evidence of biliary blockage had biliary drainage (50.00% endoscopic and 50.00% surgical). A favorable response to the intervention of oral diet tolerance was observed, with an average duration of approximately 1 day (19 hours) until the patient could tolerate a liquid diet Conclusion: The utilization of self-expandable metal stents (SEMS) in the management of gastroduodenal malig- nancies is a viable, safe, and effective strategy, especially in individuals with a limited life expectancy or in advanced disease states. This intervention facilitates improvements in both nutritional status and overall quality of life.